Biocompatibility assessment and antiproliferative activity of Detarium microcarpum Guill. and Perr. fruit pulp extracts. - Rouamba Ablassé; Nkono Ya Nkono Barnabé Lucien; Ouedraogo Vincent; Duceac Iona Alexandra; Compaoré Moussa; Ouédraogo Maurice; Kiendrebeogo Martin; Verestiuc Liliana (International Journal of Phytomedicine, 2021)
The consumption of tropical fruits rich in chemopreventive compounds are required to prevent cells carcinogenesis and proliferation. This study was designed to assess de biocompatibility of Detarium microcarpum fruit extract on normal fibroblasts and its antiproliferative potentiality on human osteosarcoma MG-63 cells. Primary dermal fibroblasts and human osteosarcoma MG-63 cells were treated with different concentrations of hexane, chloroform, ethyl acetate and methanol extracts of D. microcarpum fruit pulp for 24h, 48h and 72h. The biocompatibility property of extracts on the normal fibroblasts and its antiproliferative activity on the human osteosarcoma cells were evaluated by using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenytetrazolium bromide (MTT) assay. The biocompatibility study of D. microcarpum fruit pulp showed that the chloroform extract has exhibited the highest cytotoxic effect on normal fibroblasts followed by the ethyl acetate extract. Hexane extract wasn’t cytotoxic at concentrations of 125 and 250 µg/mL but caused more than 80 % of cell death at a concentration of 500 µg/mL. Methanol extract didn’t show a significant cytotoxic effect. Furthermore, chloroform and ethyl acetate extracts showed the best antiproliferative activity on osteosarcoma cells. A complete cell death was observed when osteosarcoma cells were treated with ethyl acetate extract at all concentrations while chloroform extract at concentrations of 250 and 500 µg/mL caused a complete cells death. Methanol extract exhibited any antiprolifarative activity. Chloroform and ethyl acetate extract of fruits pulp of D. microcapum are potent source of anticancer phytomolecules and have potential to be a promising anti-osteosarcoma extract.